Soil Test Technology for Developing Fertilizer Recommendations of Lowland Rice - Al-Jabri, Muhammad (Pengembangan Inovasi Pertanian, 2013)
Soil test technology is an invaluable tool in determining the     availability of soil nutrient status accurately in accordance with     plant requirement. Application of inorganic fertilizer continuously     at a rate that exceeds the plant needs can lead to nutrient imbalance     due to the decreasing soil pH and accumulation of P and K in     the soil resulting in nutrient disorder. This problem can be solved     by specific location nutrient management supported with soil test     technology. Utilization of soil test technology in balanced fertilizer     application needs to be supported by P and K nutrient status maps,     soil test kit, and fertilizer recommendation software. In the future,     development of soil test technology aimed to improve land     productivity and fertilizer efficiency by improving site-specific     balanced fertilizer application integratedly with inorganic and     organic fertilizers and other materials as soil conditioner. Strategies     for developing soil test technology include: (1) replacing the     original soil analysis method using a single nutrient soil analysis     (SNSA) with multi-nutrient soil analysis (MNSA) and validating     it in paddy soil in Indonesia; (2) validating and updating P and     K nutrient status maps of 1:250,000 scale and 1:50,000 scale     periodically; (3) developing soil test kit not only to measure P and     K nutrient status, but also other nutrients such as N, S, Ca, and     Mg; (4) establishing networks and linkages between soil testing     laboratories and farmer groups in order to socialize balanced     fertilizer recommendations; (5) improving the Regulation of the     Minister of Agriculture No. 40/2007 regarding to the recom-     mendation for N, P, and K fertilizer on rice to improve the accuracy     of site-specific fertilizer recommendations; and (6) closing soil     test technology to farmers as end-user to form an integrated ground     test clinic (mobile soil test). This last strategy is to complement     the achievement of good agricultural practices (GAP), which is     associated with precision farming including the nature of the soil,     plants, and site-specific fertilizer recommendations in exact rate,     time, and application method.